2011
DOI: 10.4238/vol10-3gmr1205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complete mitochondrial DNA control regions among five Asian freshwater turtle species and their phylogenetic relationships

Abstract: ABSTRACT. The complete mitochondrial DNA (mtDNA) control regions (CR), cytochrome b (Cyt b), NADH dehydrogenase subunit 4 (ND4) and cytochrome coxidase subunit I (CO I) genes of four Asian freshwater turtles, Mauremys japonica, Ocadia sinensis, M. mutica, and Annamemys annamensis, were sequenced using universal PCR and long-PCR techniques. Combined with CR sequences of Chinemys reevesii, the composition and structure of CR of the five species were compared and analyzed. Three functional domains (TAS, CD and CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Apart from the general advantages of mitochondrial markers in animal phylogenetic studies, namely their maternal inheritance, lack of recombination, and fast rate of evolution [ 9 , 10 ], several unique qualities make the CR a favoured marker sequence for genetic diversity analyses, in particular, its exceptionally fast evolutionary rate (even in comparison to the rest of the mitochondrial genome [ 11 , 12 ]), polymorphic nature [ 13 ] and presumed selective neutrality as a non-coding region (but see [ 14 , 15 ]). Consequently, this region has been widely used as a genetic marker in phylogenetic studies of various animals including vertebrate classes such as fish (e.g., [ 16 , 17 ]), amphibians [ 18 ], reptiles [ 19 ], birds [ 20 ] and mammals [ 21 , 22 ] as well as numerous invertebrate taxa (e.g., [ 23 26 ]. Nevertheless, despite being extremely useful for some species, several factors may hinder the utility of this marker in others.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the general advantages of mitochondrial markers in animal phylogenetic studies, namely their maternal inheritance, lack of recombination, and fast rate of evolution [ 9 , 10 ], several unique qualities make the CR a favoured marker sequence for genetic diversity analyses, in particular, its exceptionally fast evolutionary rate (even in comparison to the rest of the mitochondrial genome [ 11 , 12 ]), polymorphic nature [ 13 ] and presumed selective neutrality as a non-coding region (but see [ 14 , 15 ]). Consequently, this region has been widely used as a genetic marker in phylogenetic studies of various animals including vertebrate classes such as fish (e.g., [ 16 , 17 ]), amphibians [ 18 ], reptiles [ 19 ], birds [ 20 ] and mammals [ 21 , 22 ] as well as numerous invertebrate taxa (e.g., [ 23 26 ]. Nevertheless, despite being extremely useful for some species, several factors may hinder the utility of this marker in others.…”
Section: Introductionmentioning
confidence: 99%
“…D-loop sequences (∼1000 bp) analyzed in MEGA v6.06 [21] for intraspecific variations revealed 189 variable sites, 51 parsimony informative sites and only 89 conserved sites. Though D-loop is the most variable, fast evolving part of mitochondrial genome [32] , they too possess functional conserved domains preceding VNTR region like TAS, CD (CSB-F) and CSBs (1, 2 and 3) as found in mammals [33] , freshwater turtles of order- Geoemydidae [32] and Trionychidae [34] . These functional sites have been identified in the current data and their intraspecific variations are depicted in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular phylogenetic analyses have shown that the genus Ocadia is included in a clade with Chinemys spp. and Mauremys japonica and that these taxa form another more inclusive clade with the remaining living species of Mauremys (Mauremys sensu lato, Honda et al 2002;Barth et al 2004;Feldman and Parham 2004;Spinks et al 2004;Sasaki et al 2006;Jiang et al 2011). However, no synapomorphic morphological character states are known for the two clades (e.g., Honda et al 2002;Hirayama et al 2007).…”
Section: Systematicsmentioning
confidence: 99%
“…In recent molecular phylogenetic studies, this genus has been frequently synonymized with Mauremys along with Chinemys (e.g., Fritz and Havaš 2007;Turtle Taxonomy Working Group 2007;Lovich et al 2011) because O. sinensis, M. japonica and Chinemys spp. form a monophyletic clade and are included in a major, more inclusive clade with the other species of the genus Mauremys sensu stricto (Honda et al 2002;Barth et al 2004;Feldman and Parham 2004;Spinks et al 2004;Sasaki et al 2006;Jiang et al 2011). However, to date, no diagnostic morphological features or synapomorphies are known for the clade embracing O. sinensis, M. japonica, and Chinemys spp.…”
Section: Introductionmentioning
confidence: 99%